Studi Evaluasi atas Dana Talangan Haji Produk Perbankan Syariah di Indonesia - Sopa & Siti Rahmah; Siti Rahmah (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: An Evaluation Study on Haji Bridging Funds of Shariah Banking Products in Indonesia. Hajj bridging funds are one of the financing products of Islamic banking based on a fatwa of the National Shariah Council that was endorsed by the Ijtimak Ulama of Fatwâ Commission throughout Indonesia. The bridging funds are to be provided to the customers who are able to settle up the loan before the hajj. Different transactions are used in hajj bridging funds. There are transactions of ijârah, qard, or both. Hajj bridging funds provide a positive impact (maslahah) like the ease for customers to obtain the hajj departure portion. However, the disadvantage (mafsadah) of hajj bridging funds are the increasing waste of the criteria of ability (istitâ‘ah) in hajj and the extending of hajj departure waiting lists.Keywords: hajj bailout, istitâ‘ah, maslahah, transaction of ijârah, transaction of qardAbstraks: Studi Evaluasi atas Dana Talangan Haji Produk Perbankan Syariah di Indonesia. Dana talangan haji merupakan salah satu produk pembiayaan perbankan syariah yang berlandaskan fatwa Dewan Syariah Nasional yang diperkuat oleh Ijtimak Ulama Komisi Fatwa seluruh Indonesia. Dana talangan haji diberikan kepada nasabah yang mampu melunasinya sebelum melaksanakan ibadah haji. Akad yang digunakan dalam talangan haji berbeda-beda. Ada yang menggunakan akad ijârah, qard, dan gabungan keduanya. Dana talangan haji memberikan dampak positif (maslahah) berupa adanya kemudahan kepada nasabah untuk mendapatkan porsi keberangkatan haji. Sedangkan dampak negatif (mafsadah) dana talangan haji adalah semakin mengaburkan kriteria mampu (istitâ‘ah) dalam haji dan memperpanjang daftar tunggu keberangkatan haji.Kata Kunci: dana talangan haji, istitâ‘ah, maslahah, akad ijârah, akad qardDOI: 10.15408/ajis.v13i2.943